Behavioral dynamics of halal cryptocurrency investing: cognitive and emotional mechanisms within islamic finance principles - M. Syukri; Ade Sofyan Mulazid; M. Agung Rahmadi; Luthfiah Mawar; Helsa Nasution; Nurzahara Sihombing (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study comprehensively investigates the influence of cognitive biases, emotions, and Islamic legal understanding on halal cryptocurrency investment decisions among Muslim investors. Employing a Meta-Structural Equation Modeling (MASEM) approach, the analysis is based on data from 12,780 respondents in Muslim-majority countries to identify patterns of relationships among key variables. The primary findings of this research affirm that overconfidence has a significant positive impact on investment intention (β = 0.41, p < 0.01), consistent with Shiller (2017), who highlighted that excessive confidence can drive risk-taking behavior in financial markets. Conversely, loss aversion demonstrates a significant negative effect (β = -0.53, p < 0.01), aligning with Kahneman and Tversky's (2013) findings regarding preferences for avoiding losses under uncertainty. Regarding emotional factors, anxiety about price volatility is a major deterrent to investment (β = -0.54, p < 0.01). However, a Sharia-compliant label mitigates negative perceptions among Muslim investors toward cryptocurrency investments, enhancing their sense of security and trust (β = 0.36, p < 0.05). Lastly, understanding Islamic law significantly influences confidence in halal investments (β = 0.39, p < 0.05), corroborating the findings of El-Gamal (2006) and Din (2021) while underscoring the importance of Sharia-based financial literacy. The novelty of this study lies in its multidimensional integration of psychological behavior (cognitive biases and emotions) and Islamic law, thereby expanding the horizons of prior research. Consequently, this research contributes to the foundation of a new construct and provides practical guidance for developing Sharia-compliant financial products in the digital era.